Graphitic carbon nitride quantum dots: Synthesis and applications - Dang Dinh Khoi (Journal of Technical Education Science, 2021)
Graphitic-carbon nitride quantum dots (g-CNQDs), a rising star in the carbon nitride family, has shown great potential in many fields including chemical and biomedical applications due to their good biocompatibility, stable fluorescence, high quantum yield, and nontoxicity. For this reason, enormous efforts have been devoted to optimizing synthetic methods and structures of g-CNQDs to discover the inner properties and structural features in the intriguing system. Also, a vast number of studies have been pursued to discuss the potential applications of g-CNQDs in chemical and biomedical areas. In this review, recent advances in synthesis and applications of g-CNQDs were summarized and the future challenges as well as opportunities of these g-CNQDs in the chemical and biomedical fields will be highlighted.